Characterization of meiobenthos in areas of coastal influence by two companies located in the industrial zone of Mamonal, Cartagena Bay, Colombia - Osorio-Dualiby, David M.; Álvarez-León, Ricardo (Arquivos de Ciências do Mar, 2011)
A characterization of the meiobenthic in two areas of coastal influence of two companies located in the industrial zone of Mamonal was carried out, in the Bay of Cartagena, including the periods of loss and discharge salinity. The influence in the composition and the structure of the registered meiobenthic settled down that, it was related to the coastal influence of the effluents of the evaluated industries, and not by the variation of the salinity. These inferences were established from the analysis of the homogeneity of the Variance, Test of Bartlett and comparison of averages, analysis of Variance of a route with a level of confidence of (95%) and confirmation through the application of the index of Similarity of Bray Curtis. Additionally, coal particles were found, in the meiobenthic layer, in proportion of approximately 55%, with respect to the content of inorganic particles.